Experimental measurement of squeeze flow in bearings - Low, Alan Xuan Yi (2014)
This project investigates for the presence of positive pressure generation with the use of two extended spiral grooves bearings (SGB), namely 10 and 15 grooves with new geometries. As mentioned in the literature, these new geometries were designed and manufactured based on the optimum point obtained from the simulation results done by Loh [17] because the previous SGB geometries failed to generate positive pressure at the film thickness above 0.1mm. Furthermore, the area of interest in an axial clearance gap between the centrifugal rotating impeller and the stationary housing is to maintain at about 0.2mm in order to keep the power required to drive the impeller to a minimum and create a hydrodynamic lifting simultaneously. Thus, the experimental measurements were conducted for both extended SGBs in an open system, simulating the operation of ventricular assisted device (VAD) with an outflow rate of 0.01 L/min at various rotating speeds and film thicknesses. The rotating speed ranges from 300 to 2100rpm with an increment of 300rpm each time and four different film thicknesses ranges from 0.1 to 0.2mm.